2020
DOI: 10.1007/s12187-020-09782-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Household Income Affect children’s Outcomes? A Systematic Review of the Evidence

Abstract: There is abundant evidence that children in low income households do less well than their peers on a range of developmental outcomes. However, there is continuing uncertainty about how far money itself matters, and how far associations simply reflect other, unobserved, differences between richer and poorer families. The authors conducted a systematic review of studies using methods that lend themselves to causal interpretation. To be included, studies had to use Randomised Controlled Trials, quasi-experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(212 citation statements)
references
References 70 publications
7
159
1
3
Order By: Relevance
“…Discrimination may thus be an instrumental factor in ethnic health inequalities in children on an individual level and via its impact on parental SES. For example, the ‘Family Stress Model’ and the ‘Investment Model’ by which economic hardship may lead to impaired parenting abilities, poor living conditions and consumption of unhealthy foods are mechanisms through which discrimination and exclusion may impact on child health outcomes via low parental SES [59]. A growing body of research has found similar mechanisms may be at play in the Nordic context, documenting the effects of racism and discrimination on child and adult mental health and self-reported health [37,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination may thus be an instrumental factor in ethnic health inequalities in children on an individual level and via its impact on parental SES. For example, the ‘Family Stress Model’ and the ‘Investment Model’ by which economic hardship may lead to impaired parenting abilities, poor living conditions and consumption of unhealthy foods are mechanisms through which discrimination and exclusion may impact on child health outcomes via low parental SES [59]. A growing body of research has found similar mechanisms may be at play in the Nordic context, documenting the effects of racism and discrimination on child and adult mental health and self-reported health [37,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are at least two reasons to be cautious about establishing a systematic causal link between the two (Cooper & Stewart, 2013). First, there has been very few long-term studies about processes that explain this relationship.…”
Section: Family Ses and Student Academic Achievementmentioning
confidence: 99%
“…Last, the link between family SES and academic success might be indirect. Indeed, prolonged exposure to an underprivileged environment have repercussions on several variables that are themselves related to academic success (Cooper & Stewart, 2013). Among the family variables, meta-analyses have shown that parental expectations for their children’s academic success is the measure most closely related to academic success in primary and secondary school (with an effect size around .57; Fan & Chen, 2001; Jeynes, 2007).…”
Section: Family Ses and Student Academic Achievementmentioning
confidence: 99%
“…Children of poor mothers are more likely to be born small, more likely to die in the first year of life, they are less likely to be well nourished, less likely to grow well and do well in school, and they are less healthy. 6 The effects of poverty on children’s nutrition, growth, development, and health are substantial and are observed in every setting. 7 Whether in the United Sates or in Uganda, children growing up in poverty have poorer development and poorer health.…”
Section: Developmental Origins Of Health and Disease And Gender Inequmentioning
confidence: 99%